Dynamic simulation and ranking of using residential-scale solar water heater in Iran - Rezapour, Shahram; Jahangiri, Mehdi; Shahrezaie, Arezoo Ghadiri; Goli, Alireza; Farsani, Rouhollah Yadollahi; Almutairi, Khalid; Ao, Hoa Xuan; Hosseini Dehshiri, Seyyed Jalaladdin; Hosseini Dehshiri, Seyyed Shahabaddin; Mostafaeipour, Ali; Techato, Kuaanan (Journal of Environmental Engineering and Landscape Management, 2022)
A decrease in the utilization of fossil energies, mainly by replacing them with renewable energy sources (RESs), is regarded as a potential energy source in today’s applications. RESs are broadly utilized for heating purposes and particularly with applications in solar water heater (SWH). Despite the accessibility of SWH technologies and their affordable prices in Iran, there is no comprehensive study to explain the potential of Iranian regions to supply hot water for household applications. This one-year work, hence, attempts the first dynamical simulation of a solar heating system to provide sanitary hot water (SHW) as well as hot water demanded to heat 47 stations in Iran. Weather data were extracted from METEONORM and environmental-technical analyses performed by thermal solar (TSOL) software. Stations were ranked based on CCR and BCC models in data envelopment analysis (DEA) method using GAMS V 24.1. As with results, a total of 223.1 MWh solar heat is generated annually from all stations that prevent the emission of 64.5 t CO2 every year. According to CCR and BCC models, Bandar Abbas, Chabahar, Fasa, Iranshahr, Kermanshah, Khoramabad, Sarab, Shahr-e-kord, Yasuj, Zanjan, and Zahedan are the best in this regard. Also according to the economic analysis, the average price of home solar heating in Iran is 0.160 $/kWh.